2011
DOI: 10.1073/pnas.1107409108
|View full text |Cite
|
Sign up to set email alerts
|

The supply chain of CO2emissions

Abstract: CO 2 emissions from the burning of fossil fuels are conventionally attributed to the country where the emissions are produced (i.e., where the fuels are burned). However, these production-based accounts represent a single point in the value chain of fossil fuels, which may have been extracted elsewhere and may be used to provide goods or services to consumers elsewhere. We present a consistent set of carbon inventories that spans the full supply chain of global CO 2 emissions, finding that 10.2 billion tons CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
221
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 410 publications
(235 citation statements)
references
References 18 publications
2
221
0
1
Order By: Relevance
“…High level studies of global trade typically find that international trade has shifted pollution into developing countries that have used manufacturing and heavy industry to fuel their growth (Davis et al, 2011;Kanemoto et al, 2014;Peters et al, 2011b).…”
Section: The Textiles and Clothing Context: Globalisation Fast Fashimentioning
confidence: 99%
“…High level studies of global trade typically find that international trade has shifted pollution into developing countries that have used manufacturing and heavy industry to fuel their growth (Davis et al, 2011;Kanemoto et al, 2014;Peters et al, 2011b).…”
Section: The Textiles and Clothing Context: Globalisation Fast Fashimentioning
confidence: 99%
“…First, committed emissions (orange bars in Fig. 2) are estimates of future emissions from existing CO 2 -emitting infrastructure that will continue for infrastructure lifetimes without early retirement [42][43][44] …”
Section: Regional Carbon Quotasmentioning
confidence: 99%
“…Thus, any reported gain in UK material efficiency, measured by the economic ratio, would disguise the true worsening of the UK's physical material efficiency. Davis et al [40] demonstrated that this phenomenon is not limited to the UK, and report the balance of trade of CO 2 for 11 countries, strongly re-inforcing the conclusion that production-based figures are a poor indicator of a nation's environmental impacts. A further complication from the difference between economic and physical measures of material efficiency arises when the word 'material' is used to describe the intermediate inputs of production, rather than physical materials.…”
Section: Economics and Materials Efficiencymentioning
confidence: 99%